2006
DOI: 10.1021/jf060834m
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mcf-7 Breast Cancer Cells with a Red Grape Wine Polyphenol Fraction Results in Disruption of Calcium Homeostasis and Cell Cycle Arrest Causing Selective Cytotoxicity

Abstract: Food components influence the physiology by modulating gene expression and biochemical pathways within the human body. The disease-preventive roles of several fruit and vegetable components have been related to such properties. Polyphenolic components such as flavonoids are strong antioxidants and induce the expression of several xenobiotic-detoxifying enzymes. The mechanism of selective cytotoxicity induced by red grape wine polyphenols against MCF-7 breast cancer cells was investigated in relation to their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Although red wine has been reported to exert anticarcinogenic effects, including growth inhibition of some cancer cells (28,29), the underlying mechanisms and molecular targets remain unclear. In the present study, we found that RWE inhibited TPA-induced neoplastic transformation of JB6 P+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although red wine has been reported to exert anticarcinogenic effects, including growth inhibition of some cancer cells (28,29), the underlying mechanisms and molecular targets remain unclear. In the present study, we found that RWE inhibited TPA-induced neoplastic transformation of JB6 P+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its central role in calcium homeostasis, it is conceivable that RYR3 plays a role in breast calcification. Calcium channels are important for calcium homeostasis, which is associated with physiological and pathophysiological processes of the mammary gland, and may represent potential drug targets for the treatment of breast cancer (10)(11)(12).…”
mentioning
confidence: 99%
“…As noted in the introduction, there have been many studies suggesting effectiveness of berry extracts or polyphenol components against cancer cells and these have often been followed by studies unravelling the possible mechanisms for selective cytotoxicity such as influencing signal transduction pathways (41) and disruption of calcium homeostasis (22) or cell cycle control (41). However, fewer studies have incorporated controls using 'normal' cells and often these cells are non-identical or non-equivalent to the physiological origin of the cancer cells.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…In addition, ellagic acid was more cytotoxic against normal than the pre-malignant and malignant oral cell lines (20). Red wine polyphenols were equally cytotoxic against normal human mammary epithelial cells and the tumourigenic breast epithelial cell line MCF-7 (49) although sub-fractions of unknown composition showed some selectivity towards the tumourigenic cell line (22,49). On the other hand, polyphenol-rich cocoa extracts were differentially cytotoxic against prostate cancer cell lines DU145 and 22Rv1 compared to a normal prostate epithelial cell line (21).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation